Risk analysis in finance and insurance - Melʹnikov, A. V. 1953- (Chapman and Hall/CRC, 2011)
The development of quantitative methods based on stochastic analysis is a key achievement of modern financial mathematics. These methods can be extended and applied in the area of actuarial science, which leads to unified methods of risk management in finance and insurance. This interdisciplinary book presents an accessible, thorough introduction to the main ideas, methods, and techniques that transform risk management into a quantitative science. It clearly discusses many important notions and facts from mathematics, finance, and insurance, showing how these areas are interconnected. The text.
"A Chapman & Hall book.". - Includes bibliographical references (pages 303-309) and index
Keywords: Risk management; Finance; Insurance; Economics; Risk Management; Gestion du risque; Finances; Assurance; Économie politique; risk management; finance; insurance; economics; BUSINESS & ECONOMICS; Insurance; Risk Assessment & Management